2015
DOI: 10.1186/s12915-015-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

The initiation of nocturnal dormancy in Synechococcus as an active process

Abstract: BackgroundMost organisms, especially photoautotrophs, alter their behaviours in response to day–night alternations adaptively because of their great reliance on light. Upon light-to-dark transition, dramatic and universal decreases in transcription level of the majority of the genes in the genome of the unicellular cyanobacterium, Synechococcus elongatus PCC 7942 are observed. Because Synechococcus is an obligate photoautotroph, it has been generally assumed that repression of the transcription in the dark (da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…4A), as has been seen previously (9,10), and that some of these gene expression changes are (p)ppGpp-dependent (SI Appendix, Fig. S5).…”
Section: High (P)ppgpp Levels Stop Growth and Dramatically Alter Synesupporting
confidence: 80%
See 1 more Smart Citation
“…4A), as has been seen previously (9,10), and that some of these gene expression changes are (p)ppGpp-dependent (SI Appendix, Fig. S5).…”
Section: High (P)ppgpp Levels Stop Growth and Dramatically Alter Synesupporting
confidence: 80%
“…Proteins produced in the dark differ from those produced in the light (8), and recent studies have identified genes that are differentially expressed between light and dark (9,10). How the cell coordinates these transcriptional and translational changes remains largely unknown.…”
mentioning
confidence: 99%
“…To decrease the ATP/ADP ratio under conditions in which we do not normally observe foci, that is, in illuminated cultures, we used DCCD, a specific inhibitor of the F o F 1 -ATP synthase (Fig. 6B) (Takano et al, 2015). Foci were first detected 30 min after DCCD treatment, following a fast and sharp decrease in the ATP/ADP ratio, and continued to increase during the following 4 h of the experiment, when ca.…”
Section: Pii-pipx Foci Depend On a Low Atp/adp Ratio: Biochemical Andmentioning
confidence: 99%
“…Sequestering of PipX by PII at low ATP/ADP ratios would interfere with energetically expensive biological processes, decreasing transcriptional activity in the dark (Hosokawa et al, 2011;Takano et al, 2015). In addition to down regulation of NtcA target genes co-regulated by PipX (Espinosa et al, 2007;Valladares et al, 2011;Espinosa et al, 2014;Giner-Lamia et al, 2017), it would also affect the predicted signalling pathway responsible for the toxic functions of PipX in the absence of PII ( Fig.…”
Section: Environmental Importance Of Pii-pipx Complexes and Possible mentioning
confidence: 99%
“…Some photosynthetic organisms that rely exclusively on light for growth are known to halt DNA synthesis and enter a dormant state (20), or even die (21), in the absence of light. Since control of gene expression in the dark and consumption of energy metabolites are both under active control of the circadian clock in cyanobacteria (9,10,22), we hypothesized that unanticipated nightfall at clock times when energy reserves are low and metabolic rates are high could have deleterious effects. To test this hypothesis, we exposed a uniformly distributed ( Fig.…”
Section: A Subset Of Cells With Misaligned Clocks Do Not Survive the mentioning
confidence: 99%